DESAIN BAHAN AJAR BAHASA ARAB SAINS DENGAN PENDEKATAN WHOLE LANGUAGE - Ritonga, Mahyudin (EDUKASI: Jurnal Pendidikan Islam, 2017)
The writing of this article is motivated by the fact that Indonesian language material at IAIN Imam Bonjol Padang is still general, while the application of the KKNI demands the use of Arabic teaching materials according to scientific discipline. For this reason, it is necessary to develop Arabic teaching materials with certain approaches. This study needs an assessment of the development of Arabic language teaching materials based on programming languages, for which the methods used are data, data research, and techniques, techniques and interview data and documentation studies. The data analysis technique was carried out with an interactive model. The results of the study show: 1) the making of science-based Arabic teaching materials is needed because students are familiar with their scientific language, 2) the main themes in the field of Physics that can be developed in Arabic learning at the Tadris Physics Department, the material that discusses the basics, 3) Design Teaching Materials Arabic based approach Whole Language ​​that can be developed are basic physics themes designed with four skills, namely maharah al-istima', maharah al-kalam, maharah al-qiro'ah and maharah al-kitabah.